Venous thromboembolism in children with cancer – a population-based cohort study - Walker, Alex J.; Grainge, Matthew J.; Card, Timothy R.; West, Joe; Ranta, Susanna; Ludvigsson, Jonas F (Elsevier, 2014)
Introduction: Cancer is a known risk factor for venous thromboembolism (VTE) in adults, but population-based data in children are scarce.